PENGARUH PENGGUNAAN YOUTUBE KIDS TERHADAP KEMAMPUAN BERCERITA ANAK USIA DINI DI TAMAN KANAK-KANAK HANGTUAH PADANG - Yuni Lestari; Setiyo Utoyo; Asdi Wirman; Indra Yeni (STKIP Subang, 2026)
Storytelling ability is a crucial aspect of early childhood language development. However, storytelling skills among children at HangTuah Padang Kindergarten remain low. This study aimed to analyze the impact of using YouTube Kids on the storytelling abilities of young children at HangTuah Padang Kindergarten. A quantitative research method was employed using a quasi-experimental design with a pretest-posttest control group format. The study sample consisted of 20 children from Group B, divided into an experimental class and a control class. Data collection was conducted through observation using a storytelling ability checklist that had undergone validity and reliability testing. The results showed a greater improvement in storytelling ability in the experimental class (mean increase from 7.8 to 17) compared to the control class (7.0 to 14.6), with a significance value of 0.037 < 0.05. Thus, the use of YouTube Kids has a significant influence on enhancing the storytelling abilities of young children.